Elevated Expression and Activity of Sodium Leak Channel Contributes to Neuronal Sensitization of Inflammatory Pain in Rats - Li, Jia; Chen, Yali; Liu, Jin; Zhang, Donghang; Liang, Peng; Lu, Peilin; Shen, Jiefei; Miao, Changhong; Zuo, Yunxia; Zhou, Cheng (Frontiers in Molecular Neuroscience, 2021)
Inflammatory pain encompasses many clinical symptoms and there is no satisfactory therapeutic target. Neuronal hyperexcitability and/or sensitization of the primary nociceptive neurons in the dorsal root ganglion (DRG) and spinal dorsal horn are critical for the development and maintenance of inflammatory pain. The sodium leak channel (NALCN), a non-selective cation channel, mediates the background Na+ leak conductance and controls neuronal excitability. It is unknown whether abnormal activity of NALCN mediates the pathological process of inflammatory pain. Complete Freund’s adjuvant (CFA) was injected into the left footpad of rats to induce inflammatory pain. The thresholds of mechanical and thermal sensation and spontaneous pain behaviors were assessed. The expression of NALCN in DRG and spinal dorsal cord was measured. NALCN currents and the contribution of NALCN to neuronal excitability in the DRG and spinal dorsal cord were recorded using whole-cell patch-clamping recording. NALCN was abundantly expressed in neurons of the DRG and spinal dorsal cord. In acutely isolated DRG neurons and spinal cord slices from rats with CFA-induced inflammatory pain, NALCN currents and neuronal excitability were increased. Subsequently, intrathecal and sciatic nerve injection of NALCN-siRNA decreased NALCN mRNA and reverted NALCN currents to normal levels, then reduced CFA-induced neuronal excitability and alleviated pain symptoms. Furthermore, pain-related symptoms were significantly prevented by NALCN-shRNA-mediated NALCN knockdown in DRG and spinal cord. Therefore, increased expression and activity of NALCN contributed to neuronal sensitization in CFA-induced inflammatory pain. NALCN may be a novel molecular target for the control of inflammatory pain.